Hallucinations and other psychotic experiences across diagnoses: A comparison of phenomenological features. (October 2020) - Schutte, Maya J.L.; Linszen, Mascha M.J.; Marschall, Theresa M.; ffytche, Dominic H.; Koops, Sanne; van Dellen, Edwin; Heringa, Sophie M.; Slooter, Arjen J.C.; Teunisse, Rob; van den Heuvel, Odile A; Lemstra, Afina W.; Foncke, Elisabeth M.J.; et al.
Highlights: Phenomenology of psychotic experiences is not diagnosis specific. Among the major psychiatric disorders similar phenomenology of psychotic experiences was reported. Phenomenology of psychotic experiences is also quite similar within the cluster of neurodegenerative disorders. However, phenomenology differs largely between the diagnostic categories. Abstract: Although psychotic experiences are prevalent across many psychiatric, neurological, and medical disorders, investigation of these symptoms has largely been restricted to diagnostic categories. This study aims to examine phenomenological similarities and differences across a range of diagnoses. We assessed frequency, severity and phenomenology of psychotic experiences in 350 outpatients including; participants with schizophrenia spectrum disorders, hearing impairment, Parkinson's disease, Lewy Body Dementia, Alzheimer's disease, visual impairment, posttraumatic stress disorder, borderline personality disorder, and participants with recent major surgery. Psychotic phenomena were explored between these groups using the Questionnaire for Psychotic Experiences (QPE). Participants with major psychiatric disorders reported a combination of several psychotic experiences, and more severe experiences compared to all other disorders. Participants with recent major surgery or visual impairment experienced isolated visual hallucinations. Participants with hearing impairment reported isolated auditory hallucinations, whereas the neurodegenerative disorders reported visual hallucinations, occasionally in combination with hallucinations in another modality or delusions. The phenomenology between neurodegenerative disorders, and within major psychiatric disorders showed many similarities. Our findings indicate that the phenomenology of psychotic experiences is not diagnosis specific, but may rather point to the existence of various subtypes across diagnoses. These subtypes could have a different underlying etiology requiring specific treatment.